Compassionate Community of the Slums of Rocinha and Vidigal: Strategy to Help in Cancer Control - Silva , Alexandre Ernesto (2024)
There is an increasing understanding of the need for early integration of palliative care in the context of oncology, which could contribute to improve the clinical outcomes and promoting quality of life for the rising number of patients living and dying with the disease. Effective symptom control is a key part of providing effective care for these patients, promoting quality of life, reducing the harmful effects of the disease, and restoring functionality for as long as possible. Amidst the scenario of suffering and precariousness of patients living in the slums of Rocinha and Vidigal, in Rio de Janeiro, “Favela Compassiva” emerges as a driving force combined with public health and the residents themselves, to offer quality of life and a dignified death to patients with cancer and other life-threatening illnesses.